PET imaging of tissue reactions in the implanted cochlea: results of a pilot study - Deutsch, Philipp; Bankstahl, Jens P.; Mamach, Martin; Willmann, Michael; Bengel, Frank M.; Lenarz, Thomas; Berding, Georg; Scheper, Verena; Schwieger, Jana (Frontiers in Immunology, 2025)
PurposeAfter cochlear implantation, molecular processes at the electrode–nerve interface significantly influence the variability in clinical outcomes. The present study investigates molecular processes in a guinea pig model of cochlear implant (CI) using positron emission tomography/computed tomography (PET/CT) and correlates the imaging findings with histological analyses.MethodsAnimals were examined with PET in the 3 weeks and 9–12 months post-implantation using the inflammation marker [18F]FDG and, at the later time points, [68Ga]FAPI-46 as a marker for fibrosis. Tracer accumulation in the cochlea was determined from PET imaging based on the co-registered CT. Nine animals (seven with unilateral CI) were included. Uptake in non-implanted cochleae served as reference. Tissue growth around the implant was evaluated histologically.ResultsPost-implantation, [18F]FDG uptake was significantly increased when pooling early and late in investigation time points, while after 1 year, [68Ga]FAPI-46 uptake was increased inside the cochlear. Cochlear volumes measured by CT did not show significant differences between compared groups. Tissue growth around the implant was observed in all animals, with a trend toward increased growth associated with insertion depth. However, no clear correlation was observed between the extent of tissue growth and the uptake intensities of FDG and FAPI.DiscussionThe data indicate that increased accumulation of PET biomarkers in the cochlea after implantation can be detected in guinea pigs using a dedicated PET/CT. Given the high resolution of current clinical PET/CT devices, this method is expected to be suitable for use in patients, particularly for assessing the effect of anti-inflammatory or anti-fibrotic therapies.